2020
DOI: 10.15560/16.4.1025
|View full text |Cite
|
Sign up to set email alerts
|

First report on the anuran fauna of Hai Ha forest, Quang Ninh Province, Vietnam

Abstract: Two field surveys were conducted in the Hai Ha forest, Quang Ninh Province, northeastern Vietnam in 2015 and 2016. Based on mophological examinations, we provide the first list of 27 anuran species from this area. Ten species are recorded for the first time from Quang Ninh Province. The anuran fauna of Hai Ha District also contains one species listed in the IUCN Red List as Vulnerable, two species listed in the Red Data Book of Vietnam as Endangered, and two other species endemic to Vietnam (Limnonectes quangn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“… tonkinensis because the new species described here has smaller body size, longer hindlimbs, and upper eyelid width greater than interorbital space as we mentioned above. Additionally, Pham et al (2020) reported that males of A. ricketti from Hai Ha forest, Quang Ninh Province, Vietnam have vocal sacs, which is questionable and needs further confirmation because A.…”
Section: Discussionmentioning
confidence: 99%
“… tonkinensis because the new species described here has smaller body size, longer hindlimbs, and upper eyelid width greater than interorbital space as we mentioned above. Additionally, Pham et al (2020) reported that males of A. ricketti from Hai Ha forest, Quang Ninh Province, Vietnam have vocal sacs, which is questionable and needs further confirmation because A.…”
Section: Discussionmentioning
confidence: 99%
“…This also concerns followup papers which have been published based on data from Ziegler (2022), e.g., Ziegler & Vences (2002). The new name assignments also resulted in range extensions, such as the southernmost record of Odorrana bacboensis (Pham et al, 2017). In addition to the 88 amphibian and reptile species recorded by Ziegler (2002), three further records (all amphibians) are added herein, based on new collections from Ke Go Nature Reserve: Hyla simplex Boettger, 1901 (Hylidae), Kalophrynus interlineatus (Blyth, 1855) (Microhylidae) and Hylarana macrodactyla Günther, 1858 (Ranidae).…”
Section: Resultsmentioning
confidence: 96%
“…Another species (an oddscaled snake of the genus Achalinus) currently is under description by our group (Pham et al submitted). Odorrana bacboensis (Bain, Lathrop, Murphy, Orlov, andHo, 2003) Bain et al (2003), Hecht et al (2013), Pham et al (2017) Taylorana hascheana (Stoliczka, 1870) Limnonectes cf. limborgi (Sclater, 1892) Pham et al (2019Pham et al ( , 2020, Name in Ziegler (2002) Current Name changes or changes of identification also are of relevance for anuran call descriptions and larval descriptions provided in Ziegler (2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The species is listed by the International Union for Conservation of Nature (IUCN) Red List of Threatened Species as being of Least Concern (LC) (IUCN SSC Amphibian Specialist Group 2022). The species is diagnosable based on the combination of characters provided by Smith (1940), Pham et al (2017), and Ziegler et al (2006.…”
mentioning
confidence: 99%